2012
DOI: 10.1007/s10118-012-1166-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a hyperbranched polyether epoxy through one-step proton transfer polymerization and its application as a toughener for epoxy resin DGEBA

Abstract: A novel liquid hyperbranched polyether epoxy (HBPEE) based on commercially available hydroquinone (HQ) and 1,1,1-trihydroxymethylpropane triglycidyl ether (TMPGE) was synthesized through an A 2 + B 3 one-step proton transfer polymerization. In order to improve the toughness, the synthesized HBPEE was mixed with diglycidyl ether of bisphenol A (DGEBA) in different ratios to form hybrids and cured with triethylenetetramine (TETA). Thermal and mechanical properties of the cured hybrids were evaluated. Results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…The storage modulus ( E ′) and loss tangent (tan δ) of neat DGEBA and mixed epoxies containing different TFTEs as a function of temperature are shown in Figures and . Clearly, only one step change is evident on each E ′ curve, and only one peak on each tan δ curve is observed, suggesting that no obvious phase separation, which is consistent with other mixed epoxies . The absence of phase separation can be partially related to the structural similarity between TFTEs and DGEBA.…”
Section: Resultssupporting
confidence: 52%
“…The storage modulus ( E ′) and loss tangent (tan δ) of neat DGEBA and mixed epoxies containing different TFTEs as a function of temperature are shown in Figures and . Clearly, only one step change is evident on each E ′ curve, and only one peak on each tan δ curve is observed, suggesting that no obvious phase separation, which is consistent with other mixed epoxies . The absence of phase separation can be partially related to the structural similarity between TFTEs and DGEBA.…”
Section: Resultssupporting
confidence: 52%
“…40,[52][53][54][55] It is clearly seen that, in all those cases, the improvements in mechanical properties are always accompanied by apparently decreasing in T g s. In contrast, the reactive HBPEE modifier in this study exhibits balanced performance: notable improvements in mechanical properties at lower loading, moreover, still maintaining its high T g . It is worth noting that the results, in our previous study, 31 showed the optimum properties at 20 wt % loading. The toughness of the as-modified epoxy materials was improved, but their T g s decreased by 18% and the tensile strength was not promoted.…”
Section: Mechanical Properties Of Dgeba/hbpee Hybridsmentioning
confidence: 56%
“…It is worth noting that the results, in our previous study, 31 showed the optimum properties at 20 wt % loading. In most reports, 30,31,40,52,54,55 the hyperbranched modifiers used in epoxy systems were mainly constructed by masses of flexible or aliphatic chains in the backbones. In contrast, in this study, the hybrids containing 5 wt % HBPEE has reached the optimum balanced performance, and both the impact strength and tensile strength are improved without compromise of T g .…”
Section: Mechanical Properties Of Dgeba/hbpee Hybridsmentioning
confidence: 56%
See 1 more Smart Citation
“…The polymer epoxy matrix not only protects and stabilizes the central conjugated backbone of the molecule, but also prevents an intermolecular action, which in turn improves the solubility and processability without affecting their electronic characteristics [3][4][5] . Epoxy polymer matrix are known to be smart one due to their high temperature stability, chemical inertness, mechanical stability etc., which explore its application in various fields such as space, electrical and automotive coating [6,7] .…”
Section: Introductionmentioning
confidence: 99%